The effectiveness of digital learning platforms - Ulug‘bek Begali o‘g‘li Isroilov; Sultonjon Malikovich Egamov (Science and Education, 2025)
This article analyzes the role and effectiveness of digital learning platforms in modern education. It discusses how such platforms improve teaching and learning processes, enhance interactivity, and create new opportunities for both teachers and students. The article also highlights international experiences, existing challenges, and future prospects of using digital platforms in educational practice.